2020
DOI: 10.3389/fnins.2020.00838
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Approaches for the Treatment of Retinal Degenerative Diseases: Focus on CRISPR/Cas-Based Gene Editing

Abstract: Inherited retinal diseases encompass a highly heterogenous group of disorders caused by a wide range of genetic variants and with diverse clinical symptoms that converge in the common trait of retinal degeneration. Indeed, mutations in over 270 genes have been associated with some form of retinal degenerative phenotype. Given the immune privileged status of the eye, cell replacement and gene augmentation therapies have been envisioned. While some of these approaches, such as delivery of genes through recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 128 publications
0
5
0
Order By: Relevance
“…CRISPR-Cas systems for nucleic acid detection have been critically discussed by Li et al [54], Zhang et al [156], Doudna et al [141], Gallego et al [157], Gootenberg et al [158], Bonini et al [159], Collins et al [160], Wang et al [161] and other authors [145,[162][163][164][165][166][167][168][169][170][171][172][173][174][175][176]. Here, we review the main powerful, sensitive analytical methods of CRISPR-Cas: (i) fluorescence in situ hybridization (DNA-FISH) assay based CRISPR-Cas9 technique for specific targeting with SYBR green I as a fluorescent probe (detection limit 10 CFU/ml); (ii) CRISPR-Cas triggered isothermal exponential amplification reaction (CAS-EXPAR) based CRISPR-Cas9 technique and isothermal exponential amplification with SYBR green as a fluorescent probe for a large number of DNA generation and target DNA detection at attomole (aM) sensitivity; (iii) CRISPR rolling circular amplification (CRISPR-RCA) assay based CRISPR-Cas9 technique and rolling circle amplification with SYBR green as a fluorescent probe for a large number of DNA generation, amplification;…”
Section: Analytical Applications Of Crispr-cas12amentioning
confidence: 99%
“…CRISPR-Cas systems for nucleic acid detection have been critically discussed by Li et al [54], Zhang et al [156], Doudna et al [141], Gallego et al [157], Gootenberg et al [158], Bonini et al [159], Collins et al [160], Wang et al [161] and other authors [145,[162][163][164][165][166][167][168][169][170][171][172][173][174][175][176]. Here, we review the main powerful, sensitive analytical methods of CRISPR-Cas: (i) fluorescence in situ hybridization (DNA-FISH) assay based CRISPR-Cas9 technique for specific targeting with SYBR green I as a fluorescent probe (detection limit 10 CFU/ml); (ii) CRISPR-Cas triggered isothermal exponential amplification reaction (CAS-EXPAR) based CRISPR-Cas9 technique and isothermal exponential amplification with SYBR green as a fluorescent probe for a large number of DNA generation and target DNA detection at attomole (aM) sensitivity; (iii) CRISPR rolling circular amplification (CRISPR-RCA) assay based CRISPR-Cas9 technique and rolling circle amplification with SYBR green as a fluorescent probe for a large number of DNA generation, amplification;…”
Section: Analytical Applications Of Crispr-cas12amentioning
confidence: 99%
“…For a detailed overview, Gallego et al . discuss CRISPR/Cas-based gene editing approaches for IRDs ( Gallego et al, 2020 ).…”
Section: Crispr-based Gene Editing: a Brief Overviewmentioning
confidence: 99%
“…Early research seeking treatment for neurodegenerative diseases has shown that CRISPR can even be used in combination with other elements, e.g., nonpathogenic viruses, to help improve target specificity on any genomic sequences [ 105 , 106 ]. CRISPR-Cas9 may also be pooled with multiple guide RNAs, allowing the editing of multiple genes in one step.…”
Section: Beyond Therapeutic Safety and Efficacy Genome Editing Entails Polarizing Ethical And Legal Quandariesmentioning
confidence: 99%